Technical efficiency of dairy farms in rural Nigeria - Adeleye, Oluwakemi Rachael ADELEYE; Kovács, Krisztián (Applied Studies in Agribusiness and Commerce, 2022)
The study assessed the technical efficiency of Nigerian dairy farms. Information on 73 dairy farms was obtained from the General Household Survey (GHS Panel) for the year 2018-2019 wave, and the method of analysis employed include descriptive statistics and Data Envelopment Analysis Model. The findings show that not all the farms sampled are technically efficient, which means they can still utilize their input resources more effectively. The average level of technical efficiency of sampled farms was 83%; this suggests from the technical point of view that there exist an opportunity for expansion of milk production and revenue using the same level of inputs at present and putting to use effectively available technologies by 17%. Furthermore, results also show that farms that practice grazing systems, those located in the northern part of Nigeria and small farm sizes, have higher T.E. overall.JEL Classifications: Q12, Q1, R15